MODEL OF PROJECT MANAGEMENT OFFICE (PMO) FOR ORGANIZATIONS ACCOUNTABLE FOR IMPLEMENTING WATER DEPARTMENTAL PLANS IN COLOMBIA - , (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Audit reports from the Colombian General Comptroller Office showed that, in the country, project execution did not improve management indicators from the National Development Plan. To support this mission and strengthen project culture at the local level, an organizational diagnosis was carried out to establish a general model of the Project Management Office (PMO) for the Public Service Companies accountable for executing the Water Departmental Plans (WDP) in the country. Implementing a PMO in this type of company helps improve project performance rates in terms of cost, time, and scope, with quality as the cross-cutting axis of all processes; positively impacting and providing greater benefits to the population in which the organization decides to develop projects.